Immunogenicity and Safety of an MF59-adjuvanted Quadrivalent Seasonal Influenza Vaccine in Young Children at High Risk of Influenza-associated Complications: A Phase III, Randomized, Observer-blind, Multicenter Clinical Trial - Susanna Esposito (2020)
© 2020 Lippincott Williams and Wilkins. All rights reserved. Background: Vaccination against seasonal influenza is recommended for all children with a history of medical conditions placing them at increased risk of influenza-associated complications. The immunogenicity and efficacy of conventional influenza vaccines among young children are suboptimal; one strategy to enhance these is adjuvantation. We present immunogenicity and safety data for an MF59-adjuvanted quadrivalent influenza vaccine (aIIV4) in healthy children and those at a high risk of influenza-associated complications, based on the results of a recently completed phase III study. Methods: Children 6 months to 5 years of age (N = 10,644) were enrolled. The study was conducted across northern hemisphere seasons 2013-2014 and 2014-2015. Subjects received either aIIV4 or a nonadjuvanted comparator influenza vaccine. Antibody responses were assessed by hemagglutination inhibition assay against vaccine and heterologous strains. Long-term antibody persistence was assessed (ClinicalTrials.gov: NCT01964989). Results: aIIV4 induced significantly higher antibody titers than nonadjuvanted vaccine in high-risk subjects. aIIV4 antibody responses were of similar magnitude in high-risk and healthy subjects. Incidence of solicited local and systemic adverse events (AEs) was slightly higher in aIIV4 than nonadjuvanted vaccinees, in both the healthy and high-risk groups. Incidence of unsolicited AEs, serious AEs and AEs of special interest were similar for adjuvanted and nonadjuvanted vaccinees in the healthy and high-risk groups. Conclusion: aIIV4 was more immunogenic than nonadjuvanted vaccine in both the healthy and high-risk study groups. The reactogenicity and safety profiles of aIIV4 and the nonadjuvanted vaccine were acceptable and similar in 6-month- to 5-year-old high-risk and healthy children.